Does interpersonal communication mediate Patient satisfaction? - Yanti, Putri; Purnom, Sigit; Yulina, Yulina Eliza; Adriani, Evi (International Journal of Islamic Business and Management Review, 2024)
Purpose– This research attempts to examine howCompetence, Service Quality, Interpersonal Communication on BPJS Patient Satisfactionat the Major General HA Thalib Regional Hospital, Sungai Penuh City. Methodology–Data were collected from 2023 patients who filled out the questionnaire100 patients as a sample. Findings–Competence and service quality have a significant effect on interpersonal communication. Competence, service quality and interpersonal communication have a significant effect on patient satisfaction. However, competence and service quality also have an indirect relationship to patient satisfaction through interpersonal communication.The suggestion isprovide servicespatients, increasing employee empathy by listening to patient complaints and building physical closeness with patients and improving cleanliness and tidiness of the room so that it looks clean and tidy so that patients feel happy and comfortable. Novelty-There will be a positive tendency for Patient Satisfaction if Competence, Service Quality, Interpersonal Communication are all improved.